The use of traditional Chinese medicines in relieving exercise-induced fatigue - Liu, Yuzhou; Li, Congying; Shen, Xiaofei; Liu, Yue (Frontiers in Pharmacology, 2022)
Exercise-induced fatigue is a non-pathological fatigue and indicated by a reduction of muscle performance that is caused by excessive physical activity. It seriously affects the daily lives of people, in particular athletes, military personnel, and manual laborers. In recent years, increasing attention has been paid to improving the adverse effect of exercise-induced fatigue on people’s daily activities. Thus, studies and applications of traditional Chinese medicines (TCMs) in relieving exercise-induced fatigue have become the focus because of their good curative effects with fewer side effects. This review aims to document and summarize the critical and comprehensive information about the biological processes of exercise-induced fatigue, and to know the types of TCMs, their active components, and possible molecular mechanisms in alleviating exercise-induced fatigue. The peripheral and central mechanisms that cause exercise-induced fatigue have been summarized. A total of 47 exercise-induced fatigue relief TCMs have been collected, mostly including the types of visceral function regulation and emotional adjustment TCMs. Polysaccharides, terpenes, flavonoids/polyphenols are demonstrated to be the major bioactive components. The underlying molecular mechanisms are mainly related to the improvement of energy metabolism, elimination of excess metabolites, inhibition of oxidative stress and inflammatory response, regulation of HPA axis and neurotransmitters. Although current results are obtained mostly from animal models and the clinic trials are still insufficient, and a very few TCMs have been reported to possess potential hepatotoxicity. These findings still offer great reference value, and the significant efficacy in relieving exercise-induced fatigue is impossible to ignore. This review is expected to give insights into the research and development of new TCMs-derived drugs and health care products in relieving exercise-induced fatigue.